2005
DOI: 10.1074/jbc.m503624200
|View full text |Cite
|
Sign up to set email alerts
|

Protein L-Isoaspartyl Methyltransferase Catalyzes in Vivo Racemization of Aspartate-25 in Mammalian Histone H2B

Abstract: Protein L-isoaspartyl methyltransferase (PIMT) has been implicated in the repair or metabolism of proteins containing atypical L-isoaspartyl peptide bonds. The repair hypothesis is supported by previous studies demonstrating in vitro repair of isoaspartyl peptides via formation of a succinimide intermediate. Utilization of this mechanism in vivo predicts that PIMT modification sites should exhibit significant racemization as a side reaction to the main repair pathway. We therefore studied the D/L ratio of aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…In rat nucleosomes, the histone H2B was found to accumulate isoAsp in the Asp25-Gly26 bond in the N-terminal tail. In chicken nucleosomes, isoAsp accumulated mainly in histone H2A and, to a lesser extent, in histone H2B (20)(21)(22).…”
Section: Discussionmentioning
confidence: 96%
“…In rat nucleosomes, the histone H2B was found to accumulate isoAsp in the Asp25-Gly26 bond in the N-terminal tail. In chicken nucleosomes, isoAsp accumulated mainly in histone H2A and, to a lesser extent, in histone H2B (20)(21)(22).…”
Section: Discussionmentioning
confidence: 96%
“…28,29 The succinimide intermediate can also undergo racemization resulting in D-Asp residues being incorporated into the molecule. 14,30 Thus, pharmacokinetic (PK) information on the therapeutic antibody and an estimate of the kinetics of deamidation for different asparagine residues on the molecule are important for assessing the exposure and criticality of the PTM.…”
Section: Resultsmentioning
confidence: 99%
“…The earlier studies simply reported the presence of d-Asp in whole tissues, and the specific sites at which Asp residues racemize to form d-Asp were not known. Recently, the specific sites of d-Asp were identified in proteins from lens [4] [5], the b-amyloid protein in brain [9], histone of canine brain [10], and type-I collagen tellopeptide in urine [14]. We have also studied the mechanism of formation of d-Asp in a specific lens protein [21].…”
Section: D-aspmentioning
confidence: 99%